Interlaboratory Co-validation of a UPLC-ToF MS MAM Method for Truncations of a Fc Fusion Protein - Wu, Gang; Yu, Chuanfei; Tong, Qinghe; Wang, Wenbo; Huang, Xi; Li, Hao; Wang, Lan (Current Pharmaceutical Biotechnology, 2023)
Background: Peptide-Fc fusion proteins are inherently heterogeneous and complex molecules. Protein post-translational modifications (PTMs) or truncation can arise during manufacturing or product storage. Some of these product attributes could potentially impact the efficacy or safety of the bio-molecule and are thus classified as critical quality attributes (CQAs). These CQAs should be controlled in order to ensure manufacturing and quality consistency. Methods: A subunit UPLC-ToF MS based MAM method was developed for identity test and quantitatively monitored two critical quality attributes (CQAs) resulting from two truncations of that fusion protein (fragment 1 and 2). Three independent laboratories are involved in the method validation according to ICH Q2(R1), ICH Q6B, FDA and NMPA guidance. Results: This developed method fully meets the pre-defined analytical target profile (ATP), including specificity, accuracy, precision, quantitation limit, linearity, range and robustness. Three independent labs co-validate a UPLC-ToF MS based MAM method for protein drug QC release and stability testing. Conclusion: The experimental design of method validation can be a reference for LC-HRMS-based subunit MAM methods that have been widely used in the characterization of antibodies, ADCs and other protein-based biologics. This work paves the way for implementing MAM in QC with more targeted control of product quality.
Keywords: Interlaboratory